Hubungan Dukungan Sosial dengan Stres pada Mahasiswa Kedokteran yang Sedang Menjalani Masa Koas - Kurnia, Adilla; Aviani, Yolivia Irna (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Stress is one of the significant psychological problems among medical students undergoing clinical internship (koas). This condition can be triggered by academic demands, clinical practice burdens, and social interaction dynamics in the educational and healthcare environments. One factor that is thought to be related to the stress levels of koas students is the social support they receive from their surroundings. This study aims to determine the relationship between social support and stress levels among general medical coas students in West Sumatra. This study uses a quantitative approach with a correlational design. Data collection was conducted using a Likert scale through the Medical Student Stressor Questionnaire (MSSQ), which consisted of 39 statements, and the Multidimensional Scale of Perceived Social Support (MSPSS), which consisted of 11 statements. The research sample consisted of 113 medical students. Data analysis was performed using Spearman's rho correlation test. The hypothesis test results showed a correlation coefficient of −0.794 with a significance level of p = 0.000 (p < 0.05). These results indicate a strong negative relationship between social support and stress levels among medical students in West Sumatra, meaning that the higher the social support received by students, the lower their stress levels, and vice versa.